Antimicrobial properties of citrus waste-infused used cooking oil (UCO) shellac / Miradatul Najwa Muhd Rodhi ... [et al.] - Muhd Rodhi, Miradatul Najwa; Mohd Asri, Nur Zahirah ‘Ainaa’; Rozi, Abdullah Farhan; Veny, Harumi; Hamzah, Fazlena (Universiti Teknologi MARA, 2024)
The used cooking oil (UCO) and leftover citrus were combined to create a UCO shellac infused with potent antimicrobials. By converting oil and citrus waste into a value-added product, this process significantly contributes to waste reduction efforts. The efficiency of the shellac formulation was demonstrated by assessing the bactericidal activity of shellac made from UCO infused with orange (Citrus sinensis), lemon (Citrus limon), and key lime (Citrus aurantifolia) peel waste. Fourier-Transform Infrared Spectroscopy (FTIR) analysis revealed that the UCO shellac infused with citrus waste contained functional groups such as hydroxyl, alkyne, carboxylic acid, conjugated acid, aromatic ring, and primary alcohol, which contribute to its antimicrobial properties. Among the formulations evaluated, the lemon-infused UCO shellac had the highest ascorbic acid content (0.9 mg/L). When compared with other shellac formulations, including UCO infused with orange or lime waste, as well as a control shellac, the lemon-infused UCO shellac proved to be the most effective in inhibiting bacterial growth on the agar plate. On the plate treated with the lemon-infused UCO shellac, bacterial colonies started to form and begin expanding after 96 hours of culturing. This indicates that the infusion of discarded lemon peel into UCO yielded the shellac with the strongest antibacterial properties.